Time- and state-dependent fragility analysis of deteriorating reinforced concrete buildings under seismic sequences - Otárola, Kenneth; Galasso, Carmine; Gentile, Roberto; ICASP14; Iannacone, Leandro (My University, 2023)
Structural systems in seismically-active regions typically undergo multiple ground-motion sequences during their service life (including multiple mainshocks, mainshocks triggering other earthquakes on nearby fault segments, mainshock-aftershock, and aftershock-aftershock sequences). These successive ground motions can lead to severe structural/non-structural damage and significant direct/indirect earthquake-induced losses. Nevertheless, the effects of a pre-damaged state during ground-motion sequences are often neglected in assessing structural performance. Additionally, environmentally-induced deterioration mechanisms may exacerbate the consequences of such ground-motion sequences during the structural systems designed lifetime. Yet, such combined effects are commonly overlooked. This paper proposes an end-to-end computational methodology to derive time- and state-dependent fragility relationships (i.e., explicitly depending on time and the damage state achieved by a system during a first shock) for structural systems subjected to chloride-induced corrosion deterioration and earthquake-induced ground-motion sequences. To this aim, a vector-valued probabilistic seismic demand model is developed. Such a model relates the dissipated hysteretic energy in the ground-motion sequence to the maximum inter-storey drift induced by the first shock and the intensity measure of the second shock for a given corrosion deterioration level. Moreover, a vector-valued generalised logistic model is developed to estimate the probability of collapse, conditioning on the same parameters as above. An appropriate chloride-penetration model is then used to model the time-varying evolution of fragility relationships parameters using a plain Monte-Carlo approach, capturing the continuous nature of the deterioration processes (i.e., gradual and shock deterioration). The significant impact of such a multi-hazard threat on structural fragility is demonstrated by utilising a case-study reinforced concrete building. Due to deteriorating effects, reductions up to 33.3% can be noticed in the fragility median values.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED